2014
DOI: 10.1103/physrevd.90.023016
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino events at IceCube and the Fermi bubbles

Abstract: We discuss the possibility that the IceCube neutrino telescope might be observing the Fermi bubbles. If the bubbles discovered in gamma rays originate from accelerated protons, they should be strong emitters of high energy (≳GeV) neutrinos. These neutrinos are detectable as showerlike or tracklike events at a Km 3 neutrino observatory. For a primary cosmic ray flux with spectrum ∝ E −2.1 and cutoff energy at or above 10 PeV, the Fermi bubble flux substantially exceeds the atmospheric background, and could acco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 49 publications
4
67
0
1
Order By: Relevance
“…Exceptions may be made for local large diffuse sources (e.g., the Fermi bubbles [41] or the Galactic Halo [42,43]), but these models can typically explain, at most, a fraction of the data. If our data arise from an extragalactic flux produced by many isotropically distributed point sources, we can compare our all-sky flux with existing point-source limits.…”
Section: 101101 (2014) P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…Exceptions may be made for local large diffuse sources (e.g., the Fermi bubbles [41] or the Galactic Halo [42,43]), but these models can typically explain, at most, a fraction of the data. If our data arise from an extragalactic flux produced by many isotropically distributed point sources, we can compare our all-sky flux with existing point-source limits.…”
Section: 101101 (2014) P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…It has been suggested that this emission is caused by pp interactions of CRs that are injected from the Galactic center fort ∼ 1 − 10 Gyr [82]. In this model, the neutrino flux suggested from fluctuations around the Fermi bubbles can be consistent with a a power index s ν ≈ 2.2 [23,83]. On the other hand, the leptonic emission model is also viable that seems more consistent with the recent indication of a high-energy gamma-ray cutoff [84].…”
Section: Galactic Astrophysical Sourcesmentioning
confidence: 73%
“…However, the limited event statistics of the samples leave some room for Galactic contributions. Possible Galactic contributions to super-TeV neutrinos are the diffuse neutrino emission of galactic CRs [11,12,13], the joint emission of galactic PeV sources [14,15] or microquasars [16], and extended galactic structures like the Fermi Bubbles [17,11,18] or the Galactic halo [19]. A possible association with the sub-TeV diffuse galactic gamma-ray emission [20] and constraints from the non-observation of diffuse galactic PeV gamma-rays [21,11], have also been investigated.…”
Section: Pos(icrc2015)022mentioning
confidence: 99%